A comparative study to evaluate oral iron and intravenous iron sucrose for treatment of anemia in pregnancy in a poor socioeconomic region of Northeast India - Maureen P Tigga; Amulya P Debbarma (Tzu Chi Medical Journal)
Objective: The prevalence of anemia during pregnancy is as high as 80% in some sections of the Indian population. Iron therapy in different forms has been found to alleviate anemia and yield good fetomaternal outcome. This study aims to evaluate the efficacy of intravenous iron sucrose (IVIS) versus oral iron in treating anemia among the antenatal mothers attending a tertiary care center of Northeast India. Materials and Methods: One hundred women between 18 and 28 weeks of gestation with diagnosed iron-deficiency anemia and hemoglobin (Hb) of 7–10.9 g/dL were enrolled to be administered either oral ferrous sulfate 200 mg twice daily or requisite dose of IVIS 100 mg in 100 ml normal saline on alternate days. Hb and hematocrit were measured at the time of enrollment, 4th week, and 8th week of therapy. Acceptability of both the drugs based on like and dislike after interviewing the study participants was recorded. Adverse drug reactions, gestational age at delivery, and neonatal birth weight were also noted in both the groups. The results were analyzed by Student's t-test and Chi-square test. Results: Hb and hematocrit values were found to be increased in both the groups at 4th and 8th weeks. When both the groups were compared, the rise in the values was higher in the iron sucrose group (at 4th week P = 0.01 and at 8th week P = 0.00). The number of participants who reached target Hb levels at 4 weeks was 41 (82%) with oral iron and 48 (96%) with iron sucrose. In the iron sucrose group, no adverse effects were observed, suggesting its safety, and the acceptability and newborn birth weight were noted to be higher. Conclusion: IVIS was found to be more effective than oral iron therapy in treating antenatal anemia with no serious adverse drug reactions.